Producción de biofertilizante a partir de la descomposición de biomasa a través de biogestores - Muñoz Macas, Wilson Adrian (2019)
V. SUMMARY Currently the market is changing because not only are they focusing on production, but there is a greater concern for the care of the environment. Data registered by Agrocalidad until August of 2017, in our country 12,071 producers are working in the sector of organic production at a national level. Of which we have 33,921.81 organic hectares. Among the factors that influence the production of biofertilizer, is mainly the ignorance and importance of biological fertilizers in agriculture, the improper use of raw material for the production of the product. Agricultural production currently depends on pesticides and synthetic fertilizers, which generates a problem of salinity in soils, loss of microorganisms, toxicity and environmental pollution. Therefore, the general objective was to describe the importance of biofertilizers obtained from the decomposition of biomass through biogesters in agriculture. Biofertilizers are products based on beneficial microorganisms for soils, specially formed bacteria and fungi. These microorganisms live associated or in symbiosis with the plants and help them to their natural nutrition process, in addition to being soil regenerators. Biotechnology Center of the Research Directorate of the National University of Loja (UNL) together with the researcher Prometheus Dr. Roldán Torres Gutiérrez, have developed RizoSur, the first biofertilizer based on native bacteria of the Rhizobium genus generated in a higher education institution in the equator. the bad agricultural use of soils, which usually occurs in many cultivable areas, has increased the fertility problems. Biomass is considered all that wood, agricultural residues and manure that could cause degradation. Proper use of Biomass since this will depend on the quality of the biofertilizer.